Real-time implementation of fault-tolerant control using model predictive control - Miksch, Tobias; Gambier, Adrián; Badreddin, Essameddin (IFAC Proceedings Volumes, 2008)
Fault-tolerant control using model predictive control with online accommodation to recover from faults is investigated. A framework for this purpose is presented and problems that one encounters by changing the control law online like error-free tracking, feasibility and computational effort are addressed. In a real-time implementation, the model predictive controller is tested under actuator faults like saturation, freezing and total loss as well as under a structural fault.
Gesehen am 13.06.2019
Vom Autor zitiert als: Realtime performance evaluation of fault tolerant control using MPC on the three-tank system